Pengembangan Model Pembelajaran Konsep Bilangan Bagi Anak Dengan Mathematics Learning Disability di Sekolah Dasar Inklusi - Erna Suwangsih; Hafiziani Eka Putri; Suprih Widodo; Trisno Ikhwanudin (Universitas Sarjanawiyata Tamansiswa, 2018)
This research is motivated by the need for effective mathematical learning models for students with learning difficulties in math at inclusion schools. The formulation of the problem is